Virucidal effect of monogalactosyl diacylglyceride from a green microalga, Coccomyxa sp. KJ, against clinical isolates of SARS‐CoV‐2 as assessed by a plaque assay. Issue 1 (27th November 2021) - Hayashi, Kyoko; Asai, Satomi; Umezawa, Kazuo; Kakizoe, Hidehumi; Miyachi, Hayato; Morita, Masanobu; Akaike, Takaaki; Kuno, Hitoshi; Komatsu, Satoko; Watanabe, Takumi; Kawahara, Toshio
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is the causative agent of coronavirus disease 2019 (COVID‐19) and is capable of human‐to‐human transmission and rapid global spread. Thus, the establishment of high‐quality viral detection and quantification methods, and the development of anti‐SARS‐CoV‐2 agents are critical. Methods: Here, we present the rapid detection of infectious SARS‐CoV‐2 particles using a plaque assay with 0.5% agarose‐ME (Medium Electroosmosis) as an overlay medium. Results: The plaques were capable of detecting the virus within 36–40 h post‐infection. In addition, we showed that a monogalactosyl diacylglyceride isolated from a microalga ( Coccomyxa sp. KJ) could inactivate the clinical isolates of SARS‐CoV‐2 in a time‐ and concentration‐dependent manner. Conclusions: These results would allow rapid quantification of the infectious virus titers and help develop more potent virucidal agents against SARS‐CoV‐2. Abstract : We presented the rapid detection of SARS‐CoV‐2 using a plaque assay within 36–40 h post‐infection. In addition, we showed that a compound from a microalga inactivated the virus.